2022
DOI: 10.1021/acsaelm.1c01330
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Optical Properties of Threading Dislocations in n-Type 4H-SiC

Abstract: Despite the decades of development of the single-crystal growth and homoepitaxy of 4H silicon carbide (4H-SiC), high-density threading dislocations (TDs) still remain in 4H-SiC. In this work, we show that the diameters, depths, and inclination angles of molten-alkali etched pits can be employed to discriminate threading edge dislocations (TEDs), threading screw dislocations (TSDs), and threading mixed dislocations (TMDs) in 4H-SiC. The formation of etch pits of TEDs, TSDs, and TMDs during molten-alkali etching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…As shown in Figure (e), the band-edge emission at 390 nm and the broad-band emission ranging from 450 to 650 nm are found in the perfect n -type 4H-SiC [(100)] sample and the SF region. Similar to previous research, the broad-band emission is attributed to oxygen complexes in 4H-SiC. In addition, the emission band centered at 426 nm appears on the PL spectra of the SF region, which is the same as the band-edge emission of 6H-SiC. , The intensity mapping of the PL peak located at 426 nm is carried out across several horizontal-ridge SFs. As shown in Figure (f), all SFs have a higher PL intensity at 426 nm, indicating that the SFs revealed by the PCE in this work have the Si–C stacking sequence of (3,3).…”
Section: Resultssupporting
confidence: 77%
“…As shown in Figure (e), the band-edge emission at 390 nm and the broad-band emission ranging from 450 to 650 nm are found in the perfect n -type 4H-SiC [(100)] sample and the SF region. Similar to previous research, the broad-band emission is attributed to oxygen complexes in 4H-SiC. In addition, the emission band centered at 426 nm appears on the PL spectra of the SF region, which is the same as the band-edge emission of 6H-SiC. , The intensity mapping of the PL peak located at 426 nm is carried out across several horizontal-ridge SFs. As shown in Figure (f), all SFs have a higher PL intensity at 426 nm, indicating that the SFs revealed by the PCE in this work have the Si–C stacking sequence of (3,3).…”
Section: Resultssupporting
confidence: 77%
“…The absence or presence of the mixed component can be obtained by evaluating the shape and luminescence properties of a TSD etch pit. 17,32) Figure 4(a) shows the SEM images of the KOH-etched TSD-A, B, C, and D in the SiC sample. The strained atoms surrounding the dislocations are vulnerable to the attack of OH − .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the shapes and luminescence spectra of alkali-etched TSDs varied with the absence or presence of a mixed component of the Burgers vector. 17) Using the results obtained from 3D μ-XRT, SEM, and CL, the relationship between the structure and component in TSD was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Burgers vectors and dislocation-line directions, dislocations in 4H-SiC can be classified as threading edge dislocations (TEDs), threading edge dislocations (TSDs), threading edge dislocations (TMDs), and basal plane dislocations (BPDs) (Nakamura et al, 2007;Li et al, 2022;Luo et al, 2022). It has been found that all the dislocations increase the leakage current of 4H-SiC power devices, and the effect of TSDs is more prominent than those of TEDs (Wahab et al, 2000;Berechman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%